Self Awareness and Mitigation of Learning Loss on Students' Science Learning Outcomes During the Covid 19 Pandemic - Fajryani Simal; Dahlia Mahulauw; Marleny Leasa; John Rafafy Batlolona (Jurnal Penelitian Pendidikan IPA, 2022)
This study aimed to analyze the correlation between self-awareness, mitigating learning loss, and student science learning outcomes during the COVID-19 pandemic. Data was collected using a correlational study, a questionnaire, and data analysis using linear regression using the SPSS 16.00 application. The analysis results found that the correlation value or R correlation between self-awareness and learning outcomes was 0.020. The coefficient of determination (R2) was 0.000. In contrast, the regression between learning loss and learning outcomes was R, which was -0.073, the coefficient of determination (R2) was 0.005. The self-awareness regression coefficient on the correlation between self-awareness and learning outcomes is 0.018 or only 0.02%, so the equation becomes Y = 83,287 + 0.018X. In the correlation between self-awareness and learning outcomes, the regression coefficient of learning loss is -.119 or only <0, so the regression equation formed is Y = 94.480 -.199X. Therefore, it can be concluded that self-awareness has no correlation with students' cognitive learning outcomes, and there is no correlation between learning loss mitigation and student learning outcomes during the COVID-19 pandemic